Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Analysis of Swarm Behaviors Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
A grand challenge in the field of artificial life is to find a general theory of emergent self-organizing systems. In swarm systems most of the observed complexity is based on motion of simple entities. Similarly, statistical mechanics focuses on collective properties induced by the motion of many interacting particles. In this article we apply methods from statistical mechanics to swarm systems. We try to explain the emergent behavior of a simulated swarm by applying methods based on the fluctuation theorem. Empirical results indicate that swarms are able to produce negative entropy within an isolated subsystem due to frozen accidents. Individuals of a swarm are able to locally detect fluctuations of the global entropy measure and store them, if they are negative entropy productions. By accumulating these stored fluctuations over time the swarm as a whole is producing negative entropy and the system ends up in an ordered state. We claim that this indicates the existence of an inverted fluctuation theorem for emergent self-organizing dissipative systems. This approach bears the potential of general applicability.

Self-Organized Collective Decision Making: The Weighted Voter Model - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Lomuscio, Alessio; Scerri, Paul; Bazzan, Ana; Huhns, Michael (Proceedings of the 13th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2014))
Collective decision making in self-organized systems is challenging because it relies on local perception and local communication. Globally defined qualities such as consensus time and decision accuracy are both difficult to predict and difficult to guarantee. We present the weighted voter model which implements a self-organized collective decision making process. We provide an ODE model, a master equation model (numerically solved by the Gillespie algorithm), and agent-based simulations of the proposed decision-making strategy. This set of models enables us to investigate the system behavior in the thermodynamic limit and to investigate finite-size effects due to random fluctuations. Based on our results, we give minimum requirements to guarantee consensus on the optimal decision, a minimum swarm size to guarantee a certain accuracy, and we show that the proposed approach scales with system size and is robust to noise.

Evolving Prediction Machines: Collective Behaviors Based on Minimal Surprisal - Hamann, Heiko (Int. Conf. on Genetic and Evolutionary Computation (GECCO 2014))

Sorting in Swarm Robots Using Communication-Based Cluster Size Estimation - Birattari, Mauro; Dorigo, Marco; Hamann, Heiko; Garnier, Simon; Montes de Oca, Marco; Solnon, Christine; Stuetzle, Thomas; Ding, Hongli (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Derivation of a Micro-Macro Link for Collective Decision-Making Systems: Uncover Network Features Based on Drift Measurements - Khaluf, Yara; Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Bartz-Beielstein, T. (13th International Conference on Parallel Problem Solving from Nature (PPSN 2014))

Evolution of Collective Behaviors by Minimizing Surprise - Hamann, Heiko; Sayama, Hiroki; Rieffel, John; Risi, Sebastian; Doursat, Rene; Lipson, Hod (14th Int. Conf. on the Synthesis and Simulation of Living Systems (ALIFE 2014))

A Swarm Robotics Approach to Task Allocation Under Soft Deadlines and Negligible Switching Costs - Cervera, Enric; Khaluf, Yara; Birattari, Mauro; Hamann, Heiko; Pobil, Angel P. del; Chinellato, Eris; Martinez-Martin, Ester; Hallam, John; Morales, Antonio (Simulation of Adaptive Behavior (SAB 2014))

A Review Corpus for Argumentation Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor; Palakarska, Tsvetomira (Proceedings of the 15th International Conference on Intelligent Text Processing and Computational Linguistics)

Untersuchung des Erreichbarkeitsproblems in ungerichteten Graphen bezüglich den Komplexitätsklassen L und SL - Biermeier, Felix

Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Rainbow connection number of graph power and graph products - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Rainbow connection number and radius - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix
n the summer of 1994, courses at universities were supported for the first time through the use of the World Wide Web. With the introduction of this new technology, high expectations quickly arose that the established forms of teaching and learning in schools and universities would be replaced and that the institutions themselves might even prove to be superfluous. Twenty years later, it turns out that there is a great gap between hope and reality. Some of the ideas at the time that, for example, having access to the world's knowledge at any time would make textbooks superfluous, turned out to be naive in retrospect. Characteristic of the ideas at that time was the assumption that didactic and organizational problems of teaching and learning could be solved purely technically.

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Forschendes Lernen durch semantisches Positionieren - Jakoblew , Marcel; Keil, Reinhard; Winkelnkemper, Felix (Proceedings der HDI 2014)

Hypothesengeleitete Gestaltung von Benutzungsoberflächen - Keil, Reinhard; Schild, Christian

Knowledge integration processes and distributed knowledge organization - Keil, Reinhard

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Verified Service Compositions by Template-Based Construction - Walther, Sven; Wehrheim, Heike (Proceedings of the 11th International Symposium on Formal Aspects of Component Software (FACS))
Today, service compositions often need to be assembled or changed on-the-fly, which leaves only little time for quality assurance. Moreover, quality assurance is complicated by service providers only giving information on their services in terms of domain specific concepts with only limited semantic meaning. In this paper, we propose a method to construct service compositions based on pre-verifiedtemplates. Templates, given as workflow descriptions, are typed over a (domain-independent) template ontology defining concepts and predicates. Templates are proven correct using an abstract semantics, leaving the specific meaning of ontology concepts open, however, only up to given ontology rules. Construction of service compositions amounts to instantiation of templates with domain-specific services.Correctness of an instantiation can then simply be checked by verifying that the domain ontology(a) adheres to the rules of the template ontology, and (b) fulfills the constraints of the employed template.